ENHANCING HOUSEHOLD SUSTAINABILITY THROUGH REUSABLE PACKAGING: A COMMUNITY-BASED APPROACH TO REDUCING PLASTIC WASTE IN THE GREATER JAKARTA AREA - Bintang Ekananda; Anif Farida; Faridz Abdul Chalid Macap (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Plastic pollution is a critical global issue, with single-use plastic packaging contributing significantly to environmental degradation. This study examines the impact of Alner’s reusable packaging system in reducing household plastic waste and promoting sustainable consumption behaviors in Greater Jakarta. Using a mixed-methods approach, data was collected through a survey of 99 respondents and Focus Group Discussions (FGDs) with seven homemakers. Findings revealed that Alner’s system reduced household plastic waste by 138 units of single-use packaging per month and provided users with a 15% reduction in grocery expenses. Behavioral drivers, such as peer influence, convenience, and cost savings, played a pivotal role in encouraging the adoption of reusable systems, while deeper psychological motivations reinforced users’ commitment to sustainability. The study also identified opportunities for Alner to scale its impact by expanding product offerings, enhancing logistics, and leveraging community engagement. These findings underscore the potential of reusable packaging systems to address plastic pollution, foster economic and environmental benefits, and inspire a global shift toward circular consumption practices